(untitled) (Revista Sistemas de Producción Agroecológicos, 2024)
The veterinary profession faces significant challenges from the outset, as interspecies differences dictate a focus not only on systems but also on species-specific knowledge. Veterinary education prepares practitioners to address the health needs of various animals; however, the diversity of species makes it impractical for a single individual to effectively treat patients across different species without risks to both the professional and patient. This study aims to analyze the application of "cat-friendly" concepts in veterinary and zootechnical education, focusing on daily feline consultations and the challenges encountered. Through the evaluation of 528 felines over six months, utilizing the "cat-friendly" guidelines published by the International Society of Feline Medicine, the study divided the animals into three groups based on handling difficulty: easy, moderate, and difficult. It also classified them by sex, reproductive status, and age range. The findings, analyzed using the chi-square test, revealed statistically significant relationships between sex and handling difficulty, with males being harder to manage than females; age, with young adults being more challenging; and reproductive status, with neutered animals being easier to handle. These results highlight how understanding "cat-friendly" principles allows students to deepen their skills in managing and caring for feline patients, contributing to the preparation of professionals capable of addressing the unique needs of feline patients, distinct from canines.